Research on Blended Learning in Secondary Schools: Trends and Patterns (1982–2022) - Lia Agustina (Scientia Publica Media, 2024)
One of the most popular teaching strategies in modern digital age is blended learning. The purpose of this study to examine the state of blended learning research from 1982 to 2023. Analyzing yearly publications, often used keywords, most referenced papers, most publications, most active sources, most often used institutions, productive, and most contributing countries is the main goal of this study. A total of 567 papers from Scopus database were evaluated. The study’s findings indicate (1) a consistent rise in publications between 2018 and 2022, (2) “Students,” “blended learning,” “teaching,” and “e-learning” are the most often utilized terms. (3) The work of Ramadhani et al. (2019) is the most referenced document. (4) Authors that have significantly advanced blended learning research Gomes, A.S., Divayana, D.G.H., Aristovnik, A., Arifani, Y., Umek, L., Tomaževič, N., Ramdani, A., Killian, C.M., Keržič, D., Jatmiko, B. (5) The most recent source is Physics Conference Series publication. (6) Malang State University is the most prolific institution. (7) Indonesia the nation of origin of the institution that made most contribution, followed by China in second place, United States in third place, and Taiwan in fourth. It is intended that the findings of this study will serve as examples in the future.